Collusion and research joint ventures - Kaz Miyagiwa (Osaka University, Institute of Social and Economic Research (ISER), 2007)
We examine whether cooperation in R&D leads to product market collusion. Suppose that firms engage in a stochastic R&D race while maintaining the collusive equilibrium in a repeated-game framework. Innovation under competitive R&D creates inter-firm asymmetries, which destabilizes the collusive equilibrium. Innovation sharing through cooperative R&D preserves symmetries, thereby facilitating collusion. Sharing an efficient technology also increases industry profit, which contributes to the collusion stability but also raises social welfare. Interestingly, a welfare improvement is less likely if innovation leads to a large cost reduction. The effect of licensing under competition R&D is also examined.
Keywords: L12; L13; 330; Collusion; Research Joint Ventures; Innovation; R&D; Forschungskooperation; Joint Venture; Kartell; Industrieforschung; Innovation; Theorie